STUDENTS’ GRAMMATICAL COMPETENCE IN SPEAKING SKILL AT SMA MUHAMMADIYAH 3 MAKASSAR - Putri Rezkita; Radiah Hamid; Ardiana (FKIP Unismuh Makassar, 2021)
This study aims at finding out the students’ grammatical competence in speaking skills especially in the use of simple present tense at SMA Muhammadiyah 3 Makassar. The method of this research was Descriptive Quantitative Method. Data of the research were collected through speaking test. The sample of this research was class XI IPA 3 from SMA Muhammadiyah 3 Makassar. The sample was taken by using Purposive Sampling Technique.Based on the results of the research, it was found that the students’ grammar competence in speaking skill in of XI IPA of SMA Muhammadiyah 3 Makassar is categorized into poor level. It was found that the students are difficult to form the sentence well and to arrange correct sentence when speaking. It was based on the result of test given dealing with the classification of students’ score.